Work Placement for International Student Programmes (WISP): A Model of Effective Practice - Barton, G.; Hartwig, K.; Bennett, Dawn; Ferns, Sonia; Cain, M.; Campbell, M.; Jones, L.; Joseph, D.; Kavanagh, M.; Kelly, A.; Larkin, I.; O'Connor, E.; et al. (Springer, 2017)
With a marked increase in the number of international students enrolling in university programmes across the globe, it is important that personal and professional experiences are positive. Of interest is the workplace component of international students’ study programmes, as these experiences provide opportunities for students to socialise into new workplaces and cultural contexts. This chapter presents a theoretical model that takes into account the relationship between the concepts of internationalisation, professional socialisation, reflection and cultural development. It explores Knight’s (Internationalization of higher education. In: Knight J, de Wit H (eds) Quality and Internationalization in higher education. OECD, Paris, pp 13–23, 1999) work on internationalisation, research on personal and professional socialisation, effective reflective practice and the notion of cultural development (Wells M, J Community Health Nurs 17(4):189–199, 2000). We argue that an enhanced ethos approach, together with strong personal and professional student and staff agency and reflective practice, enhances the work placement experience. If all these elements are taken into account and the interrelationship between them is understood, we contend that it is more likely for workplace experiences to be positive and meaningful for all stakeholders.